Avaliação dos efeitos do laser em baixa intensidade e do ultrassom terapêutico sobre a proliferação e diferenciação de células precursoras miogênicas - Artilheiro, Paola Pelegrineli (2011)
The aim of this study was to analyze the effect of low intensity laser (LLLT) and therapeutic ultrasound (US) on the proliferation and differentiation of C2C12 myoblasts. The myoblasts were grown in culture medium Dulbecco's modified Eagle medium (DMEM) containing 10% fetal bovine serum (FBS) and induced to differentiate by replacing the culture medium by DMEM containing 2% horse serum (SC). Treatment with LLLT (780nm, 10mW 5J/cm2 for 12 and 20 seconds) and US (3 MHz, pulsed 20%, 0.2 and 0.5 W/cm2 for 5 minutes) occurred in two different moments: (1) After the process of cellular differentiation (96 h) and (2) Concomitant with the induction of cell differentiation. Cell proliferation was evaluated in two situations using the MTT method and cell differentiation was assessed 1 and 3 days in the situation of the concomitant induction of cell differentiation by means of the determination of activity of creatine kinase (CK). The results were statistically analyzed by analysis of variance (ANOVA), Dunnet test to verify differences between the control group and groups treated with LLLT and US adopting significance of p ≤ 0.05. The results showed no significant difference in the number of cells in the evaluation of treatment with LBI and US after differentiation, yet when the treatment was concomitant with differentiation, decreased cell proliferation in the laser group after 96 hours and 5J/cm2 an increase in intracellular CK activity in this same group three days after the induction of cell differentiation. In conclusion, we found that after cell differentiation both features do not alter cell proliferation during differentiation but treatment with LBI in the energy density of 5J/cm2 caused a reduction in proliferation after 96 and CK activity increased after 3 days which suggests a faster differentiation process.